Adoption of Agroforestry-Porang Model for Land Utilization under Teak Stands - Hermudananto Hermudananto; Dwiko Budi Permadi; Ratih Madya Septiana; Slamet Riyanto; Andita Aulia Pratama (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
Banyusoco village in Gunungkidul has more than 60% of its land as state forests managed by several forest farmer groups in Hutan Kemasyarakatan scheme (HKm) majority planted Teak (Tectona grandis). Problem of